EFEKTIVITAS KOMBINASI EKSTRAK DAUN MENGKUDU (Morinda citrifolia ) dan ASAM KANDIS SEBAGAI PENURUN BERAT BADAN PADA TIKUS PUTIH JANTAN GALUR Sprague-Dawley - Anggraena, Shinta Suci; Rahminiwati, Min; Effendi, E. Mulyati (-)
This study aimed to determine the effect of a combination of extracts of Noni leaves (Morinda citrifolia L) and fruit kandis (Garcinia cowa Roxb) on body weight of male rats induced by high- fat calories food Test animals were used 25 rats male Sprague Dawley strain age of 2 months with body weight ± 200 g. White mice were divided into 5 groups of 4 rats each. The treatment committed agains an obesity rats. The treatment group consisted of rats doses of 1 (8,75mg/kgBB noni leaves ekstract and sour fruit kandis 7mg/kgBB), dose II (4,75 mg/kgBB noni leaves ekstract and sour fruit kandis 3,5mg/kgBB), dose III (17,5 mg/kgBB noni leaves ekstract and sour fruit kandis 14mg/kgBB), the positive control group were given Orlistat and negative group were only given food to eat and drink. The observed parameters include weight loss, abdominal width, body length, skin fold, body mass indeks. The results showed that noni leaf extract and fruit kandis can be used as a weight loss with the most effective dose is 17,5 mg /kg BB noni leaf + 14 mg/kg BB fruit kandis with the most effective treatment is 14 days. Key words : Noni Leaf and fruit kandis, Feeding a High-Fat Calories,  Obesity Parameters, Rats male Sprague Dawley.